Critical limits of soil physical attributes for corn and black oat in a Xanthic Hapludox - Bareta Junior, Eloi; Marques Genú, Aline; Rampim, Leandro; Caldas Umburanas, Renan; Andre Pott, Cristiano (Revista Ciência Agronômica, 2021)
Soil compaction can decrease potential crop yield and is frequently found in no-till cultivation systems, but there islittle information on the critical limits of soil physical properties in these conditions, especially in subtropical soils. The objectives ofthis study were to evaluate the infl uence of tractor traffi c on soil physical properties and identifi es critical limits of soil bulk density,soil compaction degree, macro, and microporosity on crop yield of corn and black oat assessed in situ in a Xanthic Hapludox inSouthern Brazil. Tractor machine traffi c (0, 2, 5 and 20 passes) was established in no-till soil to create different soil compaction levels.Undisturbed soil samples were collected at depths of 0.00-0.05, 0.07-0.12 and 0.17-0.22 m just after tractor traffi c in two moments:before corn cultivation, and then before black oat cultivation. Under the conditions of this experiment, the 10% higher yields of cornand black oats were obtained with macroporosity above 0.10 m3 m-3 and 0.13 m3m-3, respectively. Similarly, the soil compactnessdegrees of 90% and 86% were considered critical for the corn and black oat, respectively. In addition, soil compaction by machinetraffi c reduced maize yield up to 33% and black oat biomass yield up to 44%. Our results demonstrate that growers should be awareof the consequences of machine traffi c on soil properties, as it can severely compromise crop yields, especially of corn and black oatscultivated in very clayey soil like the one evaluated in this study.